2008
DOI: 10.1542/peds.2007-2306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Accreditation Council for Graduate Medical Education Duty Hour Limits on Sleep, Work Hours, and Safety

Abstract: Total hours of work and sleep did not change after implementation of the duty hour standards. Although fewer residents were burned out, rates of medication errors, resident depression, and resident injuries and educational ratings did not improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 36 publications
3
124
2
3
Order By: Relevance
“…[16][17][18] This study present results, that night shift worker physicians have poor sleep quality and it is not different among their specialty's or seniority's in work. This result is new than in literature.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…[16][17][18] This study present results, that night shift worker physicians have poor sleep quality and it is not different among their specialty's or seniority's in work. This result is new than in literature.…”
Section: Discussionmentioning
confidence: 47%
“…[16][17][18] Suggestion is physicians won't be pass 80 hours in a week and 16-30 hours at once a shift. Thus, sleep withdrawal, medical mistakes and accidents can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…94 However, other aspects of well-being such as rates of depression do not seem to have changed between the pre-2003 period and the post-2003 period. 21,22,36,95 Prior research has demonstrated links between resident well-being and quality of patient care, 96,97 making preservation of resident well-being extremely important. This improvement in well-being may be one explanation for why some patient care parameters are improving in the post-2003 time period.…”
Section: Discussionmentioning
confidence: 99%
“…A study in pediatric residents failed to show improvement in medication errors after changes to reduce duty hours were implemented. 80 The other study showed that intercepted medication errors made by internal medicine residents were decreased after duty hour rules were initiated. 26 …”
Section: Errorsmentioning
confidence: 98%
“…Among the greatest concerns to most were the relative absence of objective data regarding the effects, both positive and negative, of the current duty hour requirements and the potential educational and economic impacts of the proposed changes. [4][5][6][7][8] …”
mentioning
confidence: 99%